Modern Methods of Identification of Non-Tuberculous Mycobacteria - G. N. Genatullina; A. L. Yasenyavskaya; M. A. Samotrueva (Антибиотики и Химиотерапия, 2025)
Recently, an active increase in the incidence of non-tuberculous mycobacteriosis has been registered, which is determined not only by the improvement of methods for detecting non-tuberculous mycobacteria, but also by a fairly high level of awareness of medical personnel. The choice of the most accurate identification method is extremely important in determining the treatment tactics, since mycobacteria with different growth rates have pronounced differences in resistance to antimicrobial drugs. The emergence of molecular genetic research methods makes it possible to identify and type most of the currently known non-tuberculous mycobacteria, as well as determine their drug sensitivity. The prevalence of mycobacteriosis, which today represents a serious problem for both clinicians and laboratory specialists, requires the development of a new strategy for its microbiological diagnostics.